2018
DOI: 10.3390/w10101351
|View full text |Cite
|
Sign up to set email alerts
|

Removal Processes of Carbamazepine in Constructed Wetlands Treating Secondary Effluent: A Review

Abstract: It is widely believed that constructed wetlands (CWs) own great potentiality as polishing wastewater treatment methods for removing carbamazepine (CBZ). Although the typical CBZ removal efficiencies in CWs are quite low, the CBZ removal performance could be improved to some extend by optimizing the CW design parameters. A comparison of current relevant studies indicates that horizontal sub-surface flow CWs (HSSF-CWs) and hybrid wetlands are attracting more interest for the treatment of CBZ wastewater. Accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 84 publications
0
7
0
Order By: Relevance
“…where q sat is the loading at saturation expressed at standard pressure and temperature (mL/g); ρ vap and ρ liq are the density for the vapour phase at standard pressure and temperature and the liquid phase at normal boiling point, respectively. Analytically, the total pore volume can also be determined through Equation (11) [176]:…”
Section: Total Pore Volumementioning
confidence: 99%
See 1 more Smart Citation
“…where q sat is the loading at saturation expressed at standard pressure and temperature (mL/g); ρ vap and ρ liq are the density for the vapour phase at standard pressure and temperature and the liquid phase at normal boiling point, respectively. Analytically, the total pore volume can also be determined through Equation (11) [176]:…”
Section: Total Pore Volumementioning
confidence: 99%
“…In the literature, different technologies for CBZ removal from contaminated water are reported [4,[11][12][13]. These technologies are mainly based on electrochemical oxidation [14,15], solar photolysis [16,17], photocatalysis [18][19][20], osmotic membrane separation [12,21], ion exchange [22,23], persulfate oxidation [24], ultrasound/persulfate anions oxidation [25], dielectric barrier discharge process [26,27] and ozone/ultraviolet/hydrogen peroxide advanced oxidation [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…CBZ dissipation is likely associated with uptake by C. flaccida plants and adsorption onto surfaces of plants and mesocosms. Chen et al (2018) reported that plant uptake generally accounts for 22.3 À 51.0% of the removal of CBZ in wetland environments planted with macrophytes like Canna species. Sorption to plant and mesocosm surfaces likely contributed to the balance of the dissipation observed.…”
Section: Cec Dissipation Trendsmentioning
confidence: 99%
“…In addition, the major concern is with regard to recalcitrant drugs, such as carbamazepine (CBZ), which persist in reclaimed water after conventional wastewater treatments [5]. Effluents from wastewater treatment plants represent the main source for the entry of CBZ into aquatic ecosystems [6]. CBZ is a drug used to treat a large number of mental diseases and compulsive disorders [5,7] and it is widely consumed worldwide, reaching up to 96% of the world pharmaceutical market [8].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, for more than a decade, CBZ has been categorized as an anthropogenic marker in aquatic environments [11]. Moreover, several studies that Water 2020, 12, 1272 2 of 10 have assessed the effects of CBZ on different living organisms indicate that this drug is among the most dangerous in aquatic ecosystems [6,[12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%